The neural basis of authenticity recognition in laughter and crying - Kosilo, M.; Costa, M.; Nuttall, H. E.; Ferreira, H. A.; Scott, S. K.; Menéres, S.; Pestana, J.; Jerónimo, R.; Prata, D. (Scientific Reports, 2021)
Deciding whether others’ emotions are genuine is essential for successful communication and social relationships. While previous fMRI studies suggested that differentiation between authentic and acted emotional expressions involves higher-order brain areas, the time course of authenticity discrimination is still unknown. To address this gap, we tested the impact of authenticity discrimination on event-related potentials (ERPs) related to emotion, motivational salience, and higher-order cognitive processing (N100, P200 and late positive complex, the LPC), using vocalised non-verbal expressions of sadness (crying) and happiness (laughter) in a 32-participant, within-subject study. Using a repeated measures 2-factor (authenticity, emotion) ANOVA, we show that N100’s amplitude was larger in response to authentic than acted vocalisations, particularly in cries, while P200’s was larger in response to acted vocalisations, particularly in laughs. We suggest these results point to two different mechanisms: (1) a larger N100 in response to authentic vocalisations is consistent with its link to emotional content and arousal (putatively larger amplitude for genuine emotional expressions); (2) a larger P200 in response to acted ones is in line with evidence relating it to motivational salience (putatively larger for ambiguous emotional expressions). Complementarily, a significant main effect of emotion was found on P200 and LPC amplitudes, in that the two were larger for laughs than cries, regardless of authenticity. Overall, we provide the first electroencephalographic examination of authenticity discrimination and propose that authenticity processing of others’ vocalisations is initiated early, along that of their emotional content or category, attesting for its evolutionary relevance for trust and bond formation.